Privacy Concerns and Information Sharing: The Perspective of the U-Shaped Curve - Hsu, Chien-Lung; Liao, Yi-Chuan; Lee, Ching-Wen; Chan, Lin Kun (Frontiers in Psychology, 2022)
Privacy concern is a key predictor of information sharing, yet, some critical issues remain ambiguous. Based on social capital theory, this study argues that the relationship between privacy concern and information sharing is a U-shaped curve. Users with privacy concern would not share their private information, however, such users would eventually share their information as long as they trust the website and its members. Furthermore, this study provides a contingency perspective to suggest that the curvilinear relationship between privacy concern and information sharing varies with the levels of system evaluation perception and personal motivation. The results show that under high level of system evaluation, the relationship between privacy concern squared and information sharing is non-significant. Conversely, in a low level of system evaluation, there is a U-shaped relationship between privacy concern and information sharing. Regarding motivation, the results were congruent with our expectation.